Centella asiatica increases B-cell lymphoma 2 expression in rat prefrontal cortex - Kuswati Kuswati; Djoko Prakosa; Brian Wasita; Nanang Wiyono (Universa Medicina, 2015)
BACKGROUNDStress is one of the factors that cause apoptosis in neuronal cells. Centellaasiatica has a neuroprotective effect that can inhibit apoptosis. This studyaimed to examine the effect of Centella asiatica ethanol extract on B-celllymphoma 2 (Bcl-2) protein expression in the prefrontal cortex of rats.METHODSAn experimental study was conducted on 34 brain tissue samples from maleSprague Dawley rats exposed to chronic restraint stress for 21 days. Thesamples were taken from following groups: non-stress group K, negativecontrol group P1 (stress + arabic gum powder), P2 (stress + C.asiatica at150 mg/kgBW), P3 (stress + C.asiatica at 300 mg/kg BW), P4 (stress +C.asiatica at 600 mg/kg body weight) and positive control group P5 (stress+ fluoxetine at 10 mg/kgBW). The samples were made into sections thatwere stained immunohistochemically using Bcl-2 antibody to determine thepercentage of cells expressing Bcl-2. Data were analyzed using one wayANOVA test followed by a post - hoc test.RESULTSThere were significant differences in mean Bcl-2 expression between thegroups receiving Centella asiatica compared with the non-stress group andstress-only group (negative control group) (p<0.05). The results werecomparable to those of the fluoxetine treatment group.CONCLUSIONThe Centella asiatica ethanol extract was able to increase Bcl-2 expressionin the prefrontal cortex of Sprague Dawley rats exposed to restraint stress.This study suggests that Centella asiatica may be useful in the treatment ofcerebral stress.